Välfärd hos hundar (Canis lupus familiaris) och katter (Felis catus) av brakycefala raser - Kossmann Lindström, Elin (SLU/Dept. of Animal Environment and Health (until 231231), 2020)
Brachycephaly is a conformation in cats and dogs developed by man through breeding. It is characterised by a short muzzle and a flat skull. A breed standard describes the conformation for each breed. The cat breeds that are classified as brachycephalic is Persian and Exotic and for dogs they are for example Pug, French bulldog, English bulldog, Boston terrier and Boxer. In Sweden Pug and French bulldog are both among the top 20 most popular breeds. The brachycephalic cats are not as popular in Sweden as the dogs are. The brachycephalic conformation is associated with several health problems and has an unfavourable impact on the welfare of the animals. In Sweden the animal welfare legislation and an ordinance on cats and dogs govern breeding with pets. Additionally, cat and dog breeders in Sweden needs a permit to breed three or more litters a year. It is the regional County Administrative Board that issues these permits. The aim of this bachelor thesis was to investigate how the brachycephalic conformations in cats and dogs affects the welfare of the animals. This thesis is a literature study. Scientific articles about brachycephaly, problems and diseases that are associated with brachycephaly and articles about animal welfare form the basis for this study. With the brachycephalic conformation comes several anatomic deformations, for example an elongated soft palate, abnormal nasopharyngeal turbinates and stenotic nares. All of these deformations could affect the breathing. If the breathing is affected, the cat or dog could have Brachycephalic obstructive airway syndrome (BOAS). Clinical signs of BOAS are among others steror, stridor, dyspnoea, cyanosis and fainting. A cat or a dog could show one or more clinical signs and the severity varies. Brachycephaly can affect more than just the airways, for example dogs can suffer from heat and exercise intolerance, both cats and dogs have a higher risk for skin, teeth and eye problems. Dystocia is another problem for brachycephalic dogs as well as brachycephalic cats. ...